2012
DOI: 10.1155/2012/716396
|View full text |Cite
|
Sign up to set email alerts
|

Opinions on Dental Erosive Lesions, Knowledge of Diagnosis, and Treatment Strategies among Norwegian Dentists: A Questionnaire Survey

Abstract: This study aimed to investigate dentists' general experience, knowledge about diagnosis, and treatment of dental erosive wear in young adults. A questionnaire was sent to 1262 Norwegian public dental health-employed dentists. The response rate was 60%. Results indicated that most dentists recorded erosive wear, half of them used a specific scoring system, and half registered lesions at the tooth surface level. Lesions were reported most often on palatal surfaces of upper anterior teeth (79% of dentists), on oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
50
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 31 publications
14
50
3
4
Order By: Relevance
“…Boys tend to prefer sour foods and drinks when compared with girls [Allesen-Holm et al, 2009]. Furthermore, boys are involved in more physical activities than girls thus being more susceptible to the modifications on the quality and quantity of saliva that occurs during intense sports [Lussi and Jaeggi, 2006;Mulic et al, 2012]. In conjunction, these characteristics may explain, at least in part, the higher occurrence of ETW among boys.…”
Section: Discussionmentioning
confidence: 99%
“…Boys tend to prefer sour foods and drinks when compared with girls [Allesen-Holm et al, 2009]. Furthermore, boys are involved in more physical activities than girls thus being more susceptible to the modifications on the quality and quantity of saliva that occurs during intense sports [Lussi and Jaeggi, 2006;Mulic et al, 2012]. In conjunction, these characteristics may explain, at least in part, the higher occurrence of ETW among boys.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the findings of two recently published Norwegian studies: participants with erosive lesions who had recently been to a dentist had not been informed about the presence of these lesions . These findings are in contrast to those of a survey on knowledge and awareness of dental erosive wear among Norwegian dentists, in which it was reported that dentists had good confidence about recording and identifying the causes of dental erosive wear . This discrepancy clearly indicates a need for increased focus on improved communication and the transfer of oral health messages between patients and dentists.…”
Section: Discussionmentioning
confidence: 99%
“…The growing market of healthier foods has coincided with the perception that the prevalence of dental enamel erosive lesions is increasing [1]. Dental erosion is a progressive loss of dental hard tissue that is not mediated by bacteria but chemically etched away from the tooth surface by acid and/or chelation [2].…”
Section: Introductionmentioning
confidence: 99%